(3eQBI GdReGf aj JGQjN GdCYjGfs - (3jhSa Hf pbrRoChrZpdj (B- (3Ch bRZdj (B- (3GHf YHO Gddg, CHh GdeXaQ, TeS GdOjf, SHW CHj GdaQL GHf GdLhRj,J (B654 (3g` s ((3Ydi Hf YjSi s)
(3ChdgG (B:s
(3jHJOi HbUI RcQjG hjMji s
(3BNQgG (B:s
(3Edi GdSfI GdSGHYI ef GdgLQI s
(3fSNI SGOSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B246 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B324s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B244 s
(3eUOQ GbJfGA GdCUd (B:s
(3eJMa GdChbGa (B(2125) s
Keywords: (3GdJGQjNs